Peran Promosi melalui Instagram, Kualitas Layanan dan Fasilitas Wisata terhadap Minat Berkunjung Kembali Wisatawan - Dianafakroh, Dianafakroh; Santi, Ira Nuriya; Syarifuddin, Umar; Evrianti, Hesti (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The study aims to determine the role of promotion through Instagram, service quality, and tourist facilities on tourists' intention to revisit Pantai Kura-Kura tourist location. The population of this quantitative study is not precisely known, so the sample was determined based on the criteria of followers of the Pantai Kura-Kura account and having visited the location. 120 respondents were then selected as a sample using non-probability sampling with a purposive sampling technique. The results of partial multiple linear regression analysis indicate that promotion through Instagram has no effect on tourists' intention to revisit Pantai Kura-Kura, while service quality and tourist facilities are proven to have a significant influence on this intention. Simultaneously, promotion through Instagram, service quality, and tourist facilities are proven to have a significant influence on tourists' intention to revisit.